Students’ preferences for print vs electronic study literature – next step after the survey in Norway - Landøy, Ane; Færevaag, Trude (Qualitative and Quantitative Methods in Libraries; Vol 8 No 1 (2019): March 2019 Issue, 2019)
Five Universities and Colleges in the Western part of Norway participated in the international survey of students’ preferences for print vs electronic study literature (Mizrachu et al, 2016). The national results were disseminated (Gastinger, Landøy, Repanovici 2015). In this paper, we describe the follow-up process after the initial survey results: Staff from the participating academic libraries were invited to a “training the trainers”-session in how to develop educational resources on electronic study literature for students. A number of academic librarians participated. We ask what the results in their own institutions have been so far, and how the teaching librarians have coped. The results of the follow-up survey will form the basis for further research and development.